Quality Analysis of Simplicia Red Ginger (Zingiber officinale Var. Rubrum) Rhizome with Different Drying Temperature - Farrel, Rizki; Aulawi, Tahrir; Darmawi, Ahmad (Talenta Publisher, 2020)
Red Ginger is ginger that is often used as a basic ingredient of herbal medicine because of its high essential oil content and the spiciest taste. Part of the Red Ginger plant that is commonly utilized is a rhizome, to maintain the quality of ginger rhizome so as not to reduce the economic value, the fresh ginger rhizome is processed first before storing or selling, one of the ways is in the form of Simplicia. The purpose of this study was to obtain the best drying temperature for the quality of red ginger simplicia. The treatments given were drying at 90oC (W1), 100oC (W2), 110oC (W3), and 120oC (W4). The study design used a nonfactorial Complete Randomized Design (RAL) consisting of 5 replications. Drying using an oven that lasts for 300 minutes. Data were analyzed by analysis of variance and if it had the real effect it was followed by Duncan's test (DMRT). Observations made were water content, ash content, starch levels, oleoresin levels, and vitamin C. The best drying results are at a temperature of 120°C at a moisture content with an average value of 3.70%, a temperature of 90°C produces the best drying at ash content with an average value of 4.79%, the starch content of 55.72%, oleoresin content of 50.79% and vitamin C 7.67%. It can be concluded that drying using a temperature of 120°C results in a better quality of Simplicia red ginger rhizome in the water content. Whereas at Ash content, the starch levels, oleoresin levels, and vitamin C, the best temperature is in the drying treatment at 90°C.